TREK-1 Regulates Cytokine Secretion from Cultured Human Alveolar Epithelial Cells Independently of Cytoskeletal Rearrangements. - Andreas Schwingshackl; Esra Roan; Bin Teng; Christopher M Waters (PLoS ONE, 2015)
TREK-1 deficient alveolar epithelial cells (AECs) secrete less IL-6, more MCP-1, and contain less F-actin. Whether these alterations in cytokine secretion and F-actin content are related remains unknown. We now hypothesized that cytokine secretion from TREK-1-deficient AECs was regulated by cytoskeletal rearrangements.We determined F-actin and α-tubulin contents of control, TREK-1-deficient and TREK-1-overexpressing human A549 cells by confocal microscopy and western blotting, and measured IL-6 and MCP-1 levels using real-time PCR and ELISA.Cytochalasin D decreased the F-actin content of control cells. Jasplakinolide increased the F-actin content of TREK-1 deficient cells, similar to the effect of TREK-1 overexpression in control cells. Treatment of control and TREK-1 deficient cells with TNF-α, a strong stimulus for IL-6 and MCP-1 secretion, had no effect on F-actin structures. The combination of TNF-α+cytochalasin D or TNF-α+jasplakinolide had no additional effect on the F-actin content or architecture when compared to cytochalasin D or jasplakinolide alone. Although TREK-1 deficient AECs contained less F-actin at baseline, quantified biochemically, they contained more α-tubulin. Exposure to nocodazole disrupted α-tubulin filaments in control and TREK-1 deficient cells, but left the overall amount of α-tubulin unchanged. Although TNF-α had no effect on the F-actin or α-tubulin contents, it increased IL-6 and MCP-1 production and secretion from control and TREK-1 deficient cells. IL-6 and MCP-1 secretions from control and TREK-1 deficient cells after TNF-α+jasplakinolide or TNF-α+nocodazole treatment was similar to the effect of TNF-α alone. Interestingly, cytochalasin D decreased TNF-α-induced IL-6 but not MCP-1 secretion from control but not TREK-1 deficient cells.Although cytochalasin D, jasplakinolide and nocodazole altered the F-actin and α-tubulin structures of control and TREK-1 deficient AEC, the changes in cytokine secretion from TREK-1 deficient cells cannot be explained by cytoskeletal rearrangements in these cells.